2020
DOI: 10.3390/app10072520
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation of Effect of Abnormal Process Conditions on Self-Piercing Riveting

Abstract: Self-piercing riveting (SPR) is one of the mechanical joining processes, and its application to Al/Fe dissimilar materials combination, which is hard to weld, is expanding in the automotive industry. The main process parameters in SPR are types of rivet and die, setting force, and rivet setting speed. Previously, the relationship between the main process parameters and output parameters such as cross-sectional characteristics and joint strength has been studied to optimize the SPR process. In practical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Zhang [ 24 ] performed self-pierce riveting of a 1 mm thick high-strength steel and aluminum alloy sheets and investigated the effect of the sequence of riveting on the dimensional stability of the product. Jeong et al [ 25 ] performed self-pierce riveting of high strength steel and aluminum alloy sheets and investigated the effect of sheet constraint conditions on the cross-sectional properties and joint strength.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [ 24 ] performed self-pierce riveting of a 1 mm thick high-strength steel and aluminum alloy sheets and investigated the effect of the sequence of riveting on the dimensional stability of the product. Jeong et al [ 25 ] performed self-pierce riveting of high strength steel and aluminum alloy sheets and investigated the effect of sheet constraint conditions on the cross-sectional properties and joint strength.…”
Section: Introductionmentioning
confidence: 99%
“…Kam et al [ 13 ] reported the type of effect of die type and joint configuration on mechanical performance, failure mode, and geometrical characteristics on SPR joints of steel and aluminum alloy. The SPR joint between dissimilar material combinations was also experimentally studied by Taek-Eon Jeong and Xiaocong He [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] It is a challenge to joint high strength steel to aluminum alloy by self‐piercing riveting (SPR) process. Jeong et al [ 13 ] studied the effects of abnormal process conditions on the SPR joints for 1 mm 590DP and 2 mm 5052‐H32. In the experimental design, six types of poor fit‐up, setting force with a variation of 5 kN, preclamping force with a variation of 3 kN, angular misalignments of ±20°, and an edge offset distance of ±5 mm were considered as abnormal process conditions.…”
Section: Introductionmentioning
confidence: 99%